Lexicalization, Ideology, and Identity in Kyai Salih Darat's Javanese Pegon Exegesis of Surah Al-Fatihah: A Critical Discourse Analysis - Segaf Baharun; Ali Wafa (Jurnal Lektur Keagamaan, 2026)
Nineteenth-century Indonesian scholars developed a distinctive mode of ijtihad by producing local Nusantara interpretations of Qur'anic exegesis. Despite extensive research on Javanese tafsir traditions, the systematic study of lexicalization as an ideological and identity-constructing mechanism remains conspicuously absent. This study addresses that gap through Critical Discourse Analysis (CDA), examining how lexicalization constructs the ideology and identity of Islam Jawa (Javanese Islam) within Kyai Salih Darat's Javanese Pegon exegesis of Surah al-Fatihah. The central research question asks: how do lexical choices in Fayd al-Rahman construct Javanese Islamic ideology and identity through the exegesis of Surah al-Fatihah? Using van Dijk's socio-cognitive framework of lexicalization, ideology, and identity, this descriptive qualitative study employs discourse-linguistic analysis of digital manuscripts. The findings disclose three lexicalization patterns: the preservation of Arabic lexical items to maintain the epistemic authority of Qur'anic referents; the adaptation of Javanese honorifics and speech-level terms to recontextualize Islamic ethics within culturally intelligible moral frameworks; and the hybridization of Arabic and Javanese expressions to negotiate localized Muslim identity while preserving doctrinal orthodoxy. These patterns demonstrate that lexicalization functions as a socio-cognitive and discursive mechanism through which religious authority, ideological meanings, and collective identity are simultaneously reproduced in vernacular Qur'anic interpretation. This study extends van Dijk's framework by demonstrating its applicability in a non-Western religious manuscript context and contributes to comparative scholarship on Islam Nusantara